Legal Education in Hungary in the period of the Kingdom of Hungary (Miscellanea Historico-Iuridica, 2018)
The author presents Genesis, the ways and aims of legal education in Hungarian universities, with a special focus on the Faculty of Law in Trnava, which was established in January 1667 (now Eötvös Loránd University in Budapest). The tradition of legal education has common European roots and is connected with the medieval foundation of universities in Bologna, where the priority was given to Roman law education. Due to the process of specialization and new tendencies in teaching in West European universities, the Hungarian universities were also modernized and enlarged. The exceptional position in education was dedicated to Roman and canonical law, but in the Kingdom of Hungary domestic national law was also taught – a practice that has existed at the Faculty of Law in Trnava from its very beginnings.